Direct, label-free, and rapid transistor-based immunodetection in whole serum - Gutiérrez-Sanz, Óscar; Andoy, Nesha M.; Filipiak, Marcin Szymon; Haustein, Natalie; Tarasov, Alexey (ACS sensors, 2017)
Transistor-based biosensors fulfill many requirements posed upon transducers for future point-of-care diagnostic devices such as scalable fabrication and label-free and real-time quantification of chemical and biological species with high sensitivity. However, the short Debye screening length in physiological samples (<1 nm) has been a major drawback so far, preventing direct measurements in serum. In this work, we demonstrate how tailoring the sensing surface with short specific biological receptors and a polymer polyethylene glycol (PEG) can strongly enhance the sensor response. In addition, the sensor performance can be dramatically improved if the measurements are performed at elevated temperatures (37 °C instead of 21 °C). With this novel approach, highly sensitive and selective detection of a representative immunosensing parameter—human thyroid-stimulating hormone—is shown over a wide measuring range with subpicomolar detection limits in whole serum. To the best of our knowledge, this is the first demonstration of direct immunodetection in whole serum using transistor-based biosensors, without the need for sample pretreatment, labeling, or washing steps. The presented sensor is low-cost, can be easily integrated into portable diagnostics devices, and offers a competitive performance compared to state-of-the-art central laboratory analyzers.
Gesehen am 17.08.2021